A Scientometric analysis of literature on Green Banking (1995-March 2019). (3rd April 2021) - Sarma, Prerana; Roy, Arup
ABSTRACT: With the rise in concern for the environment, Green Banking has received a lot of attention in recent times. This study aims to identify different dimensions of researches on Green Banking. Furthermore, an attempt is made to study the growth and geographical spread of researches on Green Banking. Relevant research outlets and keywords are analyzed in order to understand the trends in Green Banking research. The study identified 6 different dimensions namely Conceptual aspect, Legal aspect, Model aspect, Stakeholder aspect, Green Performance of Banks and Financial aspect. Results highlight that Green Banking is yet to be properly explored as only 178 articles were found in different portals. Academic interests in Green Banking have been on a rise since 2011 and have attained maximum attention in the year 2015. The Average Growth Rate of research articles published on Green Banking is 25.44%. Asia has the highest number of countries participating in research on Green Banking and has the highest number of research articles on Green Banking. Theoretical studies on Green Banking are comparatively more than the Empirical ones. Analyzing research outlets revealed that mainstream Finance journals are yet to be more active in publishing articles on Green Banking. Keyword analysis identified three key interests of researchers which are Green Banking, Sustainable Development, and Environment. Lastly scope for future research on Green Banking is identified and stated. This study provides useful insights into the nature and trend of research on Green Banking and can act as a reference point for researchers, policymakers, investors, and regulators.